EAGE Annual Conference &Amp; Exhibition Incorporating SPE Europec 2013
DOI: 10.2118/164932-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study of Salt Precipitation During Injection of CO2 Contaminated with H2S into Depleted Gas Fields in Northeast Netherlands

Abstract: Depleted gas fields are amongst the most probable candidates for subsurface storage of CO2. With proven reservoir and qualified seal these fields have retained gas over geological time scales. However, unlike methane, injection of CO2 changes the pH of the brine due to formation of carbonic acid. Subsequent dissolution/precipitation of minerals changes the porosity/permeability of reservoir and cap-rock. Thus, for adequate, safe and effective CO2 storage, the subsurface system needs to be fully understood. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Given that the bandwidth of the spectrometer is of several orders smaller than any change in I 0 ( ), ( ) and ( )l in the wavelength range studied we assume that these parameters can regarded as constant when integrating over the instrumental bandwidth. By using the above mentioned assumption and substitution of equation (3) and (4) into equation (1), the following expression for the measured absorption signal I m ( 0 ) is acquired ; (5) The signal detected by the spectrometer when the absorption path (cell) is filled with a buffer gas, I m 0 ( 0 ) can be expressed as; (6) Combining equation (5) and (6) we can obtain the following expression for the absorbance f(ν):…”
Section: =1mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the bandwidth of the spectrometer is of several orders smaller than any change in I 0 ( ), ( ) and ( )l in the wavelength range studied we assume that these parameters can regarded as constant when integrating over the instrumental bandwidth. By using the above mentioned assumption and substitution of equation (3) and (4) into equation (1), the following expression for the measured absorption signal I m ( 0 ) is acquired ; (5) The signal detected by the spectrometer when the absorption path (cell) is filled with a buffer gas, I m 0 ( 0 ) can be expressed as; (6) Combining equation (5) and (6) we can obtain the following expression for the absorbance f(ν):…”
Section: =1mentioning
confidence: 99%
“…SO 2 and H 2 S) and NO x [1,2] that may cause unwanted effects during transport and/or storage [3,4]. Recent studies have indicated that these components can cause severe corrosion problems in the presence of water and affect the brine in underground storage [5,6]. Moreover H 2 S, SO 2 and NO 2 can cause health problems and therefore only limited amounts (ppm level) are allowed in CO2 during transport.…”
Section: Introductionmentioning
confidence: 99%